SKRINING MALARIA DI WILAYAH KERJA PUSKESMAS BANYUASIN KECAMATAN LOANO KABUPATEN PURWOREJO PROPINSI JAWA TENGAH - Amani, Marhum Nur; Kadar, Abdul; Solikhah, Solikhah (Universitas Ahmad Dahlan, 2009)
Background: Operational Area of Banyuasin Public Health Service in Loano Subdistrict, Purworejo Regency, Middle Java Province, includes in endemic area which still has high rate of malaria disease and increased in this last three years. In 2005 it was founded four persons which positively suffered malaria; in 2006 it was founded 66 persons which positively suffered malaria (API 5,4 per 1000 populations) and increase the case in 2007 by 202 persons which positively suffered malaria. Screening test was necessary as initial filtering test of malaria diseases in operational area of Banyuasin Public Health Service, Loano Subdistrict, Purworejo Regency, Middle Java Province.Method: This was descriptive research using validity test for measuring the sensitivity and specificity of clinical symptoms of malaria as screening test. Technique of sample taking was conducted by consecutive sampling. Population was all of inhabitants living in operational area of Banyuasin Public Health Service, Loano Subdistrict, Purworejo Regency, Middle Java Province. Sample were the persons having periodical fever symptoms, sharp pain in joints, and nauseous symptoms in last two weeks by the amount of samples were 96 persons.Result of research: Based on validity calculation of screening test of clinical symptom of malaria, sensitivity and specificity rate of periodic fever symptom (Se:100%, Sp:100%), sharp pain on joints (Se:58,3%, Sp:96,4%), nausea (Se:100%, Sp:98,8%). Combination of symptom periodical fever and nausea have sensitivity and specificity rate of (Se:100%, Sp:98,8%), periodical fever and sharp pain on joints (Se:58,3%, Sp:96,4%), sharp pain on joints and nausea (Se:58,3%, Sp:100%), periodical fever and sharp pain on joints (Se:58,3%, Sp:100%).Conclusion: Sensitivity and specificity of the result of these three combinational symptoms, i.e. periodical fever + sharp pain on joints and nausea have sensitivity of 58,3% and specificity of 100%. It means that these three combinational symptoms can not be used as screening test of malaria by reason of it has low in sensitivity. Keywords: Screening, Sensitivity, Specificity, Malaria, Banyuasin Public Health Servic